BS ISO/IEC 12207-2. Systems and software engineering. Software life cycle processes. Part 2. Relation and mapping between ISO/IEC/IEEE 12207-1:2017 and ISO/IEC/IEEE 12207:2008 (23rd October 2019) - British Standards Institution,
No abstract available